Development of Congklak Media on Wuxing Radical Material For Chinese Language Education Students at Semarang State University - Suryani, Alfia; Pamuji, Dian Yuni; Nugroho, Yoyok; Agwinanda, Almira (Universitas Negeri Semarang, 2024)
This research is based on the observation of the use of instructional media in the Chuji Hanyu Xiezuo Xia course, which is limited to PPT and textbooks, leading to suboptimal Mandarin language learning. This is evidenced by the fact that students still struggle to understand and memorize Hanzi and their strokes. Additionally, students appear to easily become bored during lessons. Therefore, there is a need for media to assist students in learning Hanzi and its radicals. Based on these issues, the researcher developed a Congklak game as a tool for both learning and playing for students. The objectives of this research are: 1) To determine the results of the needs analysis for the Congklak game media on the Wuxing radicals material for the 2022 cohort of Mandarin Language Education students at Semarang State University, 2) To describe the prototype results of the Congklak game media on the Wuxing radicals material for the 2022 cohort of Mandarin Language Education students at Semarang State University, and 3) To describe the expert validation results of the Congklak game media on the Wuxing radicals material for the 2022 cohort of Mandarin Language Education students at Semarang State University. This research employs the Research and Development (R&D) method, consisting of five stages: 1) identification of potential and problems, 2) data collection, 3) product design, 4) design validation, and 5) design revision. This study resulted in the development of the Congklak game media to enhance students' understanding of the Wuxing radicals material. The needs assessment questionnaire results indicated that both students and lecturers agreed on the development of this media. Validation by media experts yielded an average score of 87.8 with a rating of 4, categorized as highly suitable for use. Meanwhile, validation by material experts obtained an average score of 87.9 with a rating of 4, also categorized as highly suitable for use. Based on feedback from material experts, the media was subsequently revised.